2010
DOI: 10.1038/nnano.2010.173
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid superconductor–quantum dot devices

Abstract: Advances in nanofabrication techniques have made it possible to make devices in which superconducting electrodes are connected to non-superconducting nanostructures such as quantum dots. The properties of these hybrid devices result from a combination of a macroscopic quantum phenomenon involving large numbers of electrons (superconductivity) and the ability to control single electrons, offered by quantum dots. Here we review research into electron transport and other fundamental processes that have been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
385
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(407 citation statements)
references
References 79 publications
6
385
0
4
Order By: Relevance
“…Complete control over the I c is attributed to the pseudomagnetic field-induced dephasing of the electron-hole phase-coherent Andreev processes in rippled graphene; this provides a unique route for turning off the supercurrent in JJGs, without sacrificing the junction quality in the supercurrent ON state, nor demanding infinite R n like other nanohybrid supercurrent transistors [19][20][21] . Completely tuneable hybrid superconductor graphene devices can be used for developing novel superconducting quantum information devices 23 , such as the Cooper-pair beam splitter 24,43 for quantum entanglement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete control over the I c is attributed to the pseudomagnetic field-induced dephasing of the electron-hole phase-coherent Andreev processes in rippled graphene; this provides a unique route for turning off the supercurrent in JJGs, without sacrificing the junction quality in the supercurrent ON state, nor demanding infinite R n like other nanohybrid supercurrent transistors [19][20][21] . Completely tuneable hybrid superconductor graphene devices can be used for developing novel superconducting quantum information devices 23 , such as the Cooper-pair beam splitter 24,43 for quantum entanglement.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of ripples in our junction was supported by weak antilocalization (WAL) analysis, which showed that the scattering rate by ripples was substantially enhanced near the CNP. Our study provides a key step towards developing superconducting quantum information devices 23,24 based on graphene technology 12 .…”
mentioning
confidence: 96%
“…Nevertheless, experiments suggest the existence of a regime in which quasiparticle transport dominates also in the subgap region. 21 For a quantum dot coupled to a normal and a superconducting lead, a possible explanation for the subgap features observed in Ref. 1 is given, where a carbon nanotube quantum dot is coupled to a normal and a superconducting contact.…”
Section: Introductionmentioning
confidence: 91%
“…Josephson junctions and coherent quantum transport have been attracting interest in recent years due to the development of modern nanofabrication techniques, which enable the fabrication of nanoscale hybrid superconducting devices in a broad range of design and materials. Josephson junctions realized with semiconductor nanowires (NWs) [4][5][6][7][8][9][10] have shown a high potential in different types of nanoscale devices demonstrating, for example, tunable supercurrents [5,6], the supercurrent reversal [8], and the suppression of supercurrent by hot electron injection [10]. NWs have also been used for superconducting quantum interference devices (SQUIDs) [8] and tunable Cooper pair splitters [11].…”
Section: Introductionmentioning
confidence: 99%